Audit Sistem Informasi Perpustakaan UPN "Veteran" Jawa Timur Menggunakan Framework COBIT 5.0 - Gana Sachio Sachio; Novanda Nurhandini Putri; Siti Mukaromah (Journal of Information System and Artificial Intelligence, 2023)
The implementation of an information system technology is not always applied to an agency, company, and also industrial. However, public facilities also do not escape the implementation of information system technology. One of the sectors/public facilities that apply information system technology is a place that is always there in every educational institution, namely the library. One example is the Universitas Pembangunan Nasional “Veteran” Jawa Timur’s Library which is a mine of information that we can benefit from both digitally and physically. Which is where the implementation of the information system for this library can be used for monitoring both management, book data, and also user data. This is where the information system audit plays a role in evaluating performance based on the framework used. For the analysis of the library information system audit this time, we will use COBIT 5 that focuses on assessing the implementation of information systems for visitors, especially students. At this time, all visitors, whether students, lecturers, alumni, or the general public, can visit the UPN library simply by filling out the visitor list manually. This is deemed not to be in accordance with the visitor flow chart that has been arranged by the library itself. Currently the application of scanning KTM barcodes for visiting students has not been carried out optimally, even though if the KTM scan system is used optimally it can facilitate the management of the library. And also the operational hours of the library which can still be said to be ambiguous, where the operating hours of the system have not been updated, stating that the library service hours are until 6 pm while in the field the service hours are only until 3 pm. Where information that could be important is only conveyed via social media, the library of the Universitas Pembangunan Nasional “Veteran” Jawa Timur.